2022
DOI: 10.1038/s41598-022-15963-4
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of xylo-oligosaccharides to suckling piglets promotes the growth of fiber-degrading gut bacterial populations during the lactation and nursery periods

Abstract: Modulating early-life microbial colonization through xylo-oligosacharides (XOS) supplementation represents an opportunity to accelerate the establishment of fiber-degrading microbial populations and improve intestinal health. Ninety piglets from 15 litters were orally administered once a day from d7 to d27 of lactation with either 5 mL of water (CON) or 5 mL of a solution containing 30 to 60 mg of XOS (XOS). Supplementation ceased at weaning (d28) when all piglets were fed the same commercial pre-starter diet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Both in humans and pigs, the gut microbiota structure undergoes drastic changes during the weaning phase, shifting from bacterial populations oriented to degrade metabolites present in the mother’s milk to bacterial populations adapted to degrade complex carbohydrates existent in the novel food offered at weaning [ 51 , 58 ]. Nevertheless, several studies suggest that events and interventions during the lactation period have the potential to induce long-lasting effects on the immune system programming, barrier function, and bacterial composition, which are preserved beyond weaning [ 1 , 25 , 59 , 60 ]. Studies in humans showed contrasting results regarding the long-term repercussions of the early modulation of the microbiome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both in humans and pigs, the gut microbiota structure undergoes drastic changes during the weaning phase, shifting from bacterial populations oriented to degrade metabolites present in the mother’s milk to bacterial populations adapted to degrade complex carbohydrates existent in the novel food offered at weaning [ 51 , 58 ]. Nevertheless, several studies suggest that events and interventions during the lactation period have the potential to induce long-lasting effects on the immune system programming, barrier function, and bacterial composition, which are preserved beyond weaning [ 1 , 25 , 59 , 60 ]. Studies in humans showed contrasting results regarding the long-term repercussions of the early modulation of the microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…However, interventional studies on animal models are more convincing in this respect [ 4 ]. For instance, in a previous report, we observed that the supplementation of xylooligosacharides to piglets exclusively during the lactation period stimulated the growth of fiber-degrading bacterial populations in the post-weaning period [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Okazaki et al, 1990 ; Courtin et al, 2008 ; Wang et al, 2010 ). XOS has been linked to improved fibre digestion, higher SCFA concentration, and better gut health in poultry ( Morgan et al, 2019 , 2022 ; Šimić et al, 2023 ) and swine ( Liu et al, 2018 ; González-Solé et al, 2022 ). However, the typical assumption is that microbial adaptation to XOS occurs mainly in the caecum while the ileum remains largely understudied.…”
Section: Introductionmentioning
confidence: 99%
“…The weaning transition is a critical period for mammalian growth (Holman et al, 2021;Gonzalez-Sole et al, 2022). Due to the inadequate development of immunological and digestive systems (Hughes et al, 2017), they are more susceptible to viruses and harmful bacteria, which can damage intestinal function and cause debilitating diarrhea.…”
Section: Introductionmentioning
confidence: 99%